A Comparative Study of Extra-Amniotic Saline Infusion (EASI), Foley’s Catheter and Prostaglandin E2(PGE2) gel for Pre-Induction Cervical Ripening - Dhakal, Keshar B.; Rai Dhakal, S. (Journal of Karnali Academy of Health Sciences, 2018)
Introduction: Cervical ripening is essential for successful induction of labor. The aim of the study is to compare the efficacy, safety and cost-effectiveness of extra-amniotic saline infusion, Foley’s catheter and intra-cervical PGE2 gel for pre-induction cervical ripening. Methods: A total 150 women having indications of labor induction were randomly assigned equally into three groups: EASI, Foley’s catheter and PGE2 gel. Eligible full-term pregnancy with Bishop score 4 or less was recruited for the study. Computer generated randomization method and random numbers were used to allocate cases into three groups. Data were analyzed by SPSS. The induction to cervical ripening interval, induction to delivery time, changes in the Bishop Score, mode of delivery and cost were assessed. Results: Majority of the cases was primigravida (67.3%) and the most common indication of induction was postdated pregnancy (72%). The mean time for induction to cervical ripening interval was shorter in Foley’s catheter and EASI than PGE2 (6.92 & 5.69 vs 11.08 (P<0.006). Majority of cases in Foley’s catheter and EASI achieved the Bishop score of 7 or more within 24 hours of induction as compared to PGE2 (88% & 84% vs 54%, P<0.000). The mean induction to delivery time is found shorter in EASI and Foley’s catheter than PGE2 (14.95hrs & 16.84hrs vs 23.18hrs). Conclusions: Foley’s catheter and extra-amniotic saline infusion (EASI) are the most efficacious, cost effective and safe methods of cervical ripening as compared to PGE2 gel.